Is CD25 blockade optimal in kidney transplant patients treated with basiliximab? A target‐mediated drug disposition model. Issue 7 (1st February 2022) - Le Tilly, Olivier; Gatault, Philippe; Baron, Christophe; Bejan‐Angoulvant, Theodora; Büchler, Matthias; Paintaud, Gilles; Ternant, David
Abstract : Aims: Basiliximab, an anti‐CD25 chimeric monoclonal antibody, is approved in prevention of acute kidney transplant rejection. This study aims at investigating target‐mediated pharmacokinetics of basiliximab. Methods: Data from the IDEALE study, where 16 kidney transplant patients were treated with 2 40‐ or 80‐mg basiliximab injections, were reanalysed. Basiliximab pharmacokinetics was described using a population 2‐compartment target‐mediated drug disposition model with the quasi‐steady‐state approximation. Results: Volume of distribution was significantly higher in males ( P = .029). Estimated baseline target antigen (CD25) level was lower is patients cotreated with cyclosporine ( P = .026). Conclusion: This analysis allows the first description of the target‐mediated nonlinear elimination of basiliximab. Our results suggest that cyclosporine cotreatment is associated with decreased target level and that an optimized dosing regimen may improve basiliximab effects.